2011
DOI: 10.1176/appi.ajp.2010.10020289
|View full text |Cite
|
Sign up to set email alerts
|

Altitude, Gun Ownership, Rural Areas, and Suicide

Abstract: Objective The authors recently observed a correlation between state altitude and suicide rate in the United States, which could be explained by higher rates of gun ownership and lower population density in the intermountain West. The present study evaluated the relationship between mean county and state altitude in the United States and total age-adjusted suicide rates, firearm-related suicide rates, and non-firearm-related suicide rates. The authors hypothesized that altitude would be significantly associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
117
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 22 publications
(26 reference statements)
3
117
2
3
Order By: Relevance
“…They found highly significant correlations between suicide rates and both the highest elevation in each state and the elevation of the state capital. Kim and colleagues 12 followed up this observation with a more detailed study that used a greater spatial resolution (3108 counties) and looked at a number of other variables. They performed a multiple regression analysis using elevation and 2 other factors known to be associated with suicide (population density and gun ownership) as independent factors.…”
Section: Altitude and Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…They found highly significant correlations between suicide rates and both the highest elevation in each state and the elevation of the state capital. Kim and colleagues 12 followed up this observation with a more detailed study that used a greater spatial resolution (3108 counties) and looked at a number of other variables. They performed a multiple regression analysis using elevation and 2 other factors known to be associated with suicide (population density and gun ownership) as independent factors.…”
Section: Altitude and Suicidementioning
confidence: 99%
“…Taken together, all these results provide good preliminary evidence that an association might exist between altitude and suicide. Kim and colleagues 12 suggested that the mediating mechanism might be metabolic stress associated with mild hypoxia.…”
Section: Altitude and Suicidementioning
confidence: 99%
“…National mental health surveys indicate that rates of depression and suicide, the most negative outcome of depression, are highest in the intermountain states (Mark, 2007). Recent studies suggest that altitude of residence may contribute to the increased suicide rates, independent of other risk factors such as age, gender, race, psychiatric disorders, and sociocultural factors Haws et al, 2009;Kim et al, 2011). Regional variation in suicide rates in the United States correlate directly with state peak elevation (Haws et al, 2009) and county elevation , despite the decrease in overall mortality rates with altitude .…”
Section: Introductionmentioning
confidence: 99%
“…Altitude has been reported to influence suicide rates Kim et al, 2011). In the United States of America (USA), it has been found to be an independent risk factor for suicide even when controlling for age, sex, race, median household income, gun ownership, and population density Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States of America (USA), it has been found to be an independent risk factor for suicide even when controlling for age, sex, race, median household income, gun ownership, and population density Kim et al, 2011). It was speculated that in higher altitude regions, metabolic stress with mild hypoxia might lead to a worsening of mood disorder symptoms and thus to higher suicide rates Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%